2021
DOI: 10.3389/fmicb.2021.631730
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Molds From Spoiled Dairy Products Towards Bioprotective Lactic Acid Bacteria Cultures

Abstract: Fungal spoilage of dairy products is a major concern due to food waste and economical losses, some fungal metabolites may furthermore have adverse effects on human health. The use of lactic acid bacteria (LAB) is emerging as a potential clean label alternative to chemical preservatives. Here, our aim was to characterize the growth potential at three storage temperatures (5, 16, and 25°C) of a panel of molds (four Mucor and nine Penicillium strains) isolated from dairy products, then investigate the susceptibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Besides non‐volatile compounds, volatile compounds were also speculated to contribute a lot to the overall antibacterial activity of L. plantarum cultures during milk fermentation according to previous studies (Shi and Knøchel 2021a, 2021b). To verify our hypothesis, a plate‐on‐plate system was built to assess the inhibitory effects of volatiles.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Besides non‐volatile compounds, volatile compounds were also speculated to contribute a lot to the overall antibacterial activity of L. plantarum cultures during milk fermentation according to previous studies (Shi and Knøchel 2021a, 2021b). To verify our hypothesis, a plate‐on‐plate system was built to assess the inhibitory effects of volatiles.…”
Section: Discussionmentioning
confidence: 97%
“…(2015), who found that the volatiles produced by yoghurt fermented with L. paracasei DGCC 2132 could completely inhibit the growth of two Penicillim strains for 4 days. In addition, Shi and Knøchel (2021a) demonstrated the inhibitory effect of volatile compounds produced by 12 LAB cultures on mould growth was observed, with the inhibitory effects ranging from 0% to around 60%. Thus, volatiles produced by L. plantarum could limit S. aureus growth.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations